Competitive Selection of Conformation Chirality of Water-Soluble Pillar[5]arene Induced by Amino Acid Derivatives - Chen, Yuan; Fu, Lulu; Sun, Baobao; Qian, Cheng; Wang, Ruibing; Jiang, Juli; Lin, Chen; Ma, Jing; Wang, Leyong (Organic letters, 2020)
The competitive conformation chirality of dynamically racemic water-soluble pillar[5]arene WP5 can be induced by 19 different l-amino acid ethyl ester hydrochlorides. Among them, l-Arg-OEt and 18 other l-amino acid ethyl ester hydrochlorides can induce the opposite-handedness conformation of WP5. This was ascribed to the different binding models with a side-chain moiety or ethyl ester moiety of amino acids toward the cavity of WP5.